Complexity, entropy, and the physics of information : the proceedings of the 1988 Workshop on Complexity, Entropy, and the Physics of Information held May-June, 1989, in Santa Fe, New Mexico /: the proceedings of the 1988 Workshop on Complexity, Entropy, and the Physics of Information held May-June, 1989, in Santa Fe, New Mexico. (2018) - Unknown
No abstract available